Visual-based UGV pose optimization in dynamic warehouse environment - Tang, Andreas Zhao Xiang (Nanyang Technological University, 2023)
Visual-based UGV pose optimization is a fascinating field that is capturing the attention of many people. With the ever-growing presence of UGVs in various industries, the need for accurate and dependable UGV pose estimation is becoming increasingly critical. This has resulted in the development of a range of methods for estimating UGV pose based on visual data, including feature detection and matching, optical flow, and SLAM algorithms. These techniques operate by examining visual data captured by cameras on the UGV and using this information to determine the UGV's position and orientation relative to its surroundings. Nonetheless, developing reliable and robust visual-based UGV pose estimation algorithms is an intricate and demanding process. Elements such as sensor noise, lighting conditions, and environmental variability can all influence the accuracy and reliability of UGV pose estimation, necessitating careful attention during the algorithm development phase. Furthermore, different UGV applications may have varying needs regarding pose estimation accuracy and real-time performance, increasing the complexity of the development process. Despite these difficulties, the potential benefits of visual-based UGV pose optimization are considerable. By enabling UGVs to navigate autonomously and accurately, these algorithms have the potential to enhance the safety and efficiency of various applications, from transportation and logistics to surveillance and security. Furthermore, as UGV technology continues to advance, the requirement for dependable and precise UGV pose estimation is anticipated to rise. Therefore, it is imperative to continue improving visual-based UGV pose optimization algorithms, to address the ever-changing demands of this exciting field.